The Effect of Circuit Training on Leg Muscle Power During the Crouch Start in the 60-Meter Dash - Isah Indayanti; Khafid Irkham (Jurnal Muara Olahraga, 2026)
This study was motivated by the observation that most students are still unable to complete tasks quickly. This study employs a quantitative approach using a quasi-experimental design. The study population consisted of 30 students participating in the 60-meter sprint track and field extracurricular program at MI Miftahunnajah Pakikiran. The students participating in the track and field program were from grades III, IV, and V. Sampling was conducted using purposive sampling, resulting in a sample of 10 students. The results of this study indicate that the circuit training method has an effect on the 60-meter sprint performance of students in the track and field extracurricular program at MI Miftahunnajah Pakikiran. This can be demonstrated through a T-test hypothesis test. Since the significance value is 0.000 < 0.05, H0 is rejected and H1 is accepted. The mean score on the pretest was 6.486, while on the posttest it was 5.656 (an increase of 0.829), resulting in a 1.658% increase. Based on the conclusions reached, the most appropriate recommendation is: (1) The need for a fundamental and comprehensive exploration of sprint training methods so that the exercises can be properly applied and tailored to the athletes’ needs: (2) The need for new innovations in the form of resources that can motivate students in the track and field training program at MI Miftahunnajah Pakikiran.